Pemberdayaan Masyarakat Kecamatan Nawangan, Kabupaten Pacitan Melalui Penganekaragaman Olahan Daun Cincau Hitam - Ardhea Mustika Sari; Sumani Sumani; Diffah Hanim; Supriyadi Supriyadi (PRIMA: Journal of Community Empowering and Services, 2018)
Black cincau leaf (Mesona palustris BL) is one of the main commodities of Nawangan District, Pacitan Regency which has high fiber and antioxidant content. In general, the cincau leaves produced at Nawangan are only sold in the form of dried leaves so that their economic value is low. Processing of dried black grass jelly leaves into processed food products can increase its economic value. The problem faced by the Nawangan community in an effort to increase the economic value of cincau leaves is that the Nawangan people do not yet have the skills and knowledge regarding various forms of processed which have a higher selling value. Through the Community Empowerment Community Service program, efforts are made to diversify processed products of black cincau leaves in the form of pastry products (nastar and cookies). This program aims to improve the skills of the Nawangan community in processing black cincau leaves into several food products that have high selling value. This activity was carried out in three stages, namely socialization, implementation of training and monitoring. The outputs produced in this activity are processed products of black cincau leaves which are expected to be the superior products of the Nawangan District.